Rancang Bangun Prototype Kelembaban Tanah - Imam Mahdi; Dian Kasoni (Jurnal Teknik Informatika, 2019)
Abstract—Apart from its name as a maritime country, Indonesia is also an agricultural country with fertile land and it has 2 seasons, rainy and dry. In the rainy season, food crops are usually not necessary to be watered because they already have received enough water. But in the dry season, they must be regularly watered because of the soil moisture conditions. The dependence of farmers on these seasons causes the production of farmers to decrease and become an obstacle to soil moisture. To overcome these obstacles and make farmers can still plant crops in the dry season, a product of information and communication technology-based agricultural equipment is needed. It is a programmable microcontroller chip that can automatically control plants watering based on soil moisture detected using soil moisture sensors. The development method used in this study is the prototype model and the programming language used is Arduino. The purpose of the tool is to detect whether the planting ground is dry so that the device can control watering automatically when the soil lacks water. This prototype was applied to realize a smart garden in utilizing technological advancements.Intisari - Indonesia selain sebagai negara maritim juga merupakan negara agraris dengan lahan yang subur dengan 2 musim yaitu musim penghujan dan musim kemarau. Pada musim penghujan biasanya tanaman pangan tidak perlu dilakukan penyiraman karena telah mendapatkan air yang cukup, sedangkan pada musim kemarau tanaman harus disiram dengan teratur sesuai dengan kondisi kelembaban tanah. Ketergantungan petani dengan musim menyebabkan produksi petani menurun dan menjadi kendala kelembaban tanah. Untuk mengatasi kendala tersebut agar petani tetap bisa bercocok tanam pada musim kemarau maka diperlukan suatu produk alat pertanian berbasis teknologi informasi dan komunikasi berupa chip mircrocontroller yang diprogram sehingga bisa mengontrol penyiraman tanaman secara otomatis berdasarkan kelembaban tanah yang dideteksi menggunakan sensor kelembaban tanah. Metode pengembangan yang digunakan pada penelitian ini dengan model prototype dan bahasa pemrograman yang digunakan adalah Arduino. Tujuan Alat untuk mendeteksi apakah tanah tempat bercocok tanam itu kering sehingga alat dapat mengontrol penyiraman secara otomatis saat tanah kekurangan unsur air. Prototype ini diaplikasikan untuk mewujudkan smart garden dalam memanfaatkan kemajuan teknologi.